Chromosome analysis of foetal tissue from 1903 spontaneous abortion patients in 5 regions of China: a retrospective multicentre study - Jian Zhang; Fangxiang Mu; Zhongjie Guo; Zhuhua Cai; Xianghui Zeng; Lirong Du; Fang Wang (BMC Pregnancy and Childbirth, 2023)
Abstract Background Abnormal foetal tissue chromosome karyotypes are one of the important pathogenic factors for spontaneous abortion (SA). To investigate the age and abnormal foetal karyotypes of 1903 couples who experienced SA. Methods A retrospective multicentre study collected age and foetal tissue karyotypes CNV-seq data of 1903 SA couples from 6 hospitals in 5 regions from January 2017 to March 2022. The distribution and correlation of abnormal foetal tissue karyotypes were evaluated by using regions and age. Results In our study, 1140 couples (60.5% of the total) had abnormal foetal tissue chromosome karyotypes in all regions. We found that there were differences in the number of abnormal foetal tissue chromosome karyotypes, of which the incidence of trisomy was higher. At the same time, the populations situated in the eastern region had a more triploid (15.5%) distribution, trisomy (58.1%) in the southern region, mosaicism (14.8%) and microduplication (31.7%) in the southwestern region, microdeletion (16.7%) in the northern region. There are variances across areas, and it is more common in the north. The incidence risk of prenatal chromosomal abnormalities varied according to age group. Conclusion The findings of this study suggest that the karyotypes of patients with abnormal foetal tissue chromosome abortion in different regions were different. Meanwhile, patients ≥ 35 years old had a higher risk of abnormal foetal tissue chromosome abortion.